2018
DOI: 10.1097/md.0000000000012630
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban improves hidden blood loss, blood transfusion rate and reduces swelling of the knee joint in knee osteoarthritis patients after total knee replacement

Abstract: Osteoarthritis (OA) is the third most common diagnosis made by general practitioners in older patients. The purpose of the current study is to investigate effects rivaroxaban had on both hidden blood loss and blood transfusion rate (BTR) in patients with knee OA (KOA) after going through a total knee replacement (TKR).Between the time periods of December 2011 up until January 2015, a total of 235 patients underwent TKR and were selected to be assigned to either the rivaroxaban or nonanticoagulant groups. Coagu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The SBP and MAP levels at T2, T3, and T4 and the HR levels at T3 and T4 were also significantly lower in patients treated with the combined selective tibial nerve plus saphenous nerve block compared with the group given single general anesthesia. The VAS is an important index commonly used in clinical practice to assess the degree of pain, and the higher the score, the more severe the pain [ 20 , 21 ]. Moreover, there was no significant difference in the incidence of adverse reactions between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…The SBP and MAP levels at T2, T3, and T4 and the HR levels at T3 and T4 were also significantly lower in patients treated with the combined selective tibial nerve plus saphenous nerve block compared with the group given single general anesthesia. The VAS is an important index commonly used in clinical practice to assess the degree of pain, and the higher the score, the more severe the pain [ 20 , 21 ]. Moreover, there was no significant difference in the incidence of adverse reactions between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that excluded surgical-site bleeding from their definition of major bleeding reported major bleeding rates approximately 10 times lower than those studies that included it. In certain RCTs assessing rivaroxaban, 74,97,98,115,116 the definition of major bleeding did not encompass surgical-site bleeding. The majority of trials involving rivaroxaban and apixaban used the hemoglobin level on the first postoperative day as a baseline (to avoid the confounder of intraoperative blood loss) to identify significant drops in hemoglobin as indicative of major bleeding.…”
Section: Discussionmentioning
confidence: 99%